Analisis Isi Buku Teks Aqidah Akhlak Kelas 4 Sampai 6 dalam Implementasi Kurikulum 2013 di Madrasah Ibtidaiyah Miftahul Huda Depok - Asyjarina Hasyyatil Hakim; Henri Peranginangin Tanjung; Abdur Rahim (Journal on Education, 2023)
This research discusses the analysis of the contents of textbooks for the Aqidah Morals grades 4 through 6 in the implementation of the 2013 curriculum at Madrasah Ibtidaiyah Miftahul Huda, Depok. This research is motivated by the change in curriculum from the 2006 curriculum to the 2013 curriculum which also causes changes to the textbooks used as a reference. This study aims to determine and describe the analysis of the content of Aqeedah Akhlak grade 4 to 6 textbooks according to MoRA publishers in terms of content assessment, and language. This research is a qualitative approach, while the type of research used is descriptive because the results of this research are presented in the form of words, where the data obtained comes from relevant documents such as books and certain writings. The data source that the researchers used was a document review, by analyzing the textbooks of moral values of grades 4 through 6. The results of this study indicate that the assessment in the 2013 Grade 4 Aqeedah Morals Textbook in terms of content eligibility, in general this textbook is in accordance with indicators of the suitability of the contents of the book based on curriculum criteria 2013, because it is in accordance with the Core Competencies and Basic Competencies in the relevant textbooks , the material is also quite short, dense and clear to know in outline. However, the lack of examples or information contained in the material. Assessment in terms of the feasibility of the language of this textbook is quite appropriate overall with the level of development of students, but there are still only a few words that are not in accordance with the level of development of students.